LES FACTEURS DU DEVELOPPEMENT DE L’HEVEACULTURE EN COTE D’IVOIRE DE 1994 A 2012 - Brindoumi Atta Kouame Jacob (European Scientific Journal, ESJ, 2015)
When the State had hired the liberalization of the sector of the rubber trees in 1994, many observers of economic life had announced its decadence. Indeed, unlike other sectors, the development of the rubber trees was possible to the strong involvement of the State as well in financing the creation of village plantations in the promotion of the agro-industrial complexes of rubber.But with the withdrawal of the State, the different actors undertake the restructuring of the sector. Professional associations, as well as of financial structures have been created. A new pricing mechanism favorable to growers purchasing price is introduced in 1999. Funding for research, management and financing of the village sector are carried out by all the different actors of the sector.